Decision aids to prepare patients for shared decision making: Two randomized controlled experiments on the impact of awareness of preference‐sensitivity and personal motives - Simone Korger; Marie Eggeling; Ulrike Cress; Joachim Kimmerle; Martina Bientzle (Wiley, 2021)
Abstract Objective To participate in shared decision making (SDM), patients need to understand their options and develop trust in their own decision‐making abilities. Two experiments investigated the potential of decision aids (DAs) in preparing patients for SDM by raising awareness of preference‐sensitivity (Study 1) and showing possible personal motives for decision making (Study 2) in addition to providing information about the treatment options. Methods Participants (Study 1: N = 117; Study 2: N = 217) were put into two scenarios (Study 1: cruciate ligament rupture; Study 2: contraception), watched a consultation video and were randomized into one of three groups where they received additional information in the form of (a) narrative patient testimonials; (b) non‐narrative decision strategies; and (c) an unrelated text (control group). Results Participants who viewed the patient testimonials or decision strategies felt better prepared for a decision (Study 1: P < .001, ηP2 = 0.43; Study 2: P < .001, ηP2 = 0.57) and evaluated the decision‐making process more positively (Study 2: P < .001, ηP2 = 0.13) than participants in the control condition. Decision certainty (Study 1: P < .001, ηP2 = 0.05) and satisfaction (Study 1: P < .001, ηP2 = 0.11; Study 2: P = .003, d = 0.29) were higher across all conditions after watching the consultation video, and certainty and satisfaction were lower in the control condition (Study 2: P < .001, ηP2 = 0.05). Discussion Decision aids that explain preference‐sensitivity and personal motives can be beneficial for improving people's feelings of being prepared and their perception of the decision‐making process. To reach decision certainty and satisfaction, being well informed of one's options is particularly relevant. We discuss the implications of our findings for future research and the design of DAs.